Profitability in Banks Affiliated to a Business Group: Evidence from Mexico. Issue 8 (2nd August 2016) - Chavarín, Rubén
ABSTRACT: In certain institutional contexts, where there are business groups, banks affiliated to these business networks are faced by incentives that might condition their profitability. The objective of this article is to test whether there is a difference between the performance of affiliated banks and that of banks not affiliated to groups, in the context of an emerging market. In particular, a study is made of the case of Mexico in the period 2007–11. Findings suggest that banks affiliated to business groups show less profitability than non-affiliated banks, which may be a consequence of the provision of loans in an internal capital market.